2018
DOI: 10.18488/journal.101.2018.51.1.10
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Selected Ecosystem Services: A Case Study of East Mau Forest Ecosystem, Kenya

Abstract: The ecosystem services from Kenya's forest ecosystems have remained largely unmeasured and undervalued. Consequently, the benefits they provide are ignored in most forest management and conservation decisions. This has led to degradation and conversion to alternative uses. To provide a sound basis for decision making in forest management, it is important to estimate economic values provided by East Mau. This study relied on data collected from households using structured interviews and secondary data from publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…These correspond to KES 620,200/(US$5796.3) and KES 1,600,000/($14953.30) per hectare per year for Elgeyo and Nyambene, respectively (Table 2). The study's estimates were higher compared to a study in the Mau East ecosystem (Langat, 2016), which reported a watershed protection value of KES 127893.11 (US$1421.03) ha −1 •yr −1 , and a study in Indonesia which estimated water flow regulation and maintenance services value at US$1880 ha −1 •yr −1 (range of $707 -3110 ha −1 •yr −1 ) (Aulia et al, 2020). Similarly, the study estimates were higher than the study value in China (Xi, 2009) between US$540 and US$560 per hectare per year.…”
Section: Watershed Protectioncontrasting
confidence: 76%
See 3 more Smart Citations
“…These correspond to KES 620,200/(US$5796.3) and KES 1,600,000/($14953.30) per hectare per year for Elgeyo and Nyambene, respectively (Table 2). The study's estimates were higher compared to a study in the Mau East ecosystem (Langat, 2016), which reported a watershed protection value of KES 127893.11 (US$1421.03) ha −1 •yr −1 , and a study in Indonesia which estimated water flow regulation and maintenance services value at US$1880 ha −1 •yr −1 (range of $707 -3110 ha −1 •yr −1 ) (Aulia et al, 2020). Similarly, the study estimates were higher than the study value in China (Xi, 2009) between US$540 and US$560 per hectare per year.…”
Section: Watershed Protectioncontrasting
confidence: 76%
“…Estimates for Elgeyo were lower and consistent with the Mengla-Shangyon and Nabanhe-Mangao corridor studies (China) in Nyambene with a unit value of US$2195 per hectare per year (Xi, 2009). A similar scenario compared to the East Mau study that assessed carbon sequestration valued at $2782.47 per hectare per year (Langat, 2016). The study mainly attributed the difference between the degraded forest of Elgeyo and the fairly well-preserved forest of Nyambene.…”
Section: Forest Tree Carbonmentioning
confidence: 91%
See 2 more Smart Citations
“…Senyawa yang bersifat termolabil sangat cocok diekstraksi dengan metode MAE. Jika dibandingkan dengan ekstraksi maserasi, MAE bisa meningkatkan hasil ekstraksi dengan waktu singkat serta pelarut yang lebih sedikit (Langat, 2011). Ramayani et al, (2021)…”
Section: Mae Adalah Ekstraksi Yang Menggunakanunclassified